- PENGEMBANGAN BUKU AJAR MEMBACA DAN MENULIS UNTUK SISWA PRASEKOLAH DASAR - Agus Saripudin; supriyadi supriyadi; marwan pulungan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2022)
The purpose of this research was to develop a reading and writing teaching material which was suitable for preschool students. The results of interview, questionnaire, and preliminary observation show that many state and private primary schools required prospective first-graders to possess the ability to read and write. The results also show that the prospective first graders in general do not have this ability. They only had the ability to recognize letters although they had completed education at TK (kindergarten) or PAUD (early childhood education program). Unsuprisingly, many TK/PAUD and tutoring teachers and parents looked for a textbook that can effectively assist teaching prospective grade-1 students to read and write. The research method used in this study was development research (RD) as highlighted by Sugiyono, with 10 steps. The research subjects were teaching and learning books on beginning reading and writing for elementary preschool students. In general, the book's principle refers to the iqro method, beginning with reading a picture, then introducing three productive letters/syllables. The three letters/ syllables are arranged into words (open syllables) followed by repetition exercises. Gradually, the next one-letter/syllable is then introduced into a word, which is then arranged into sentences, and so on. The next stage is to introduce closed letters/syllables and double letters, then to arrange them into words, and words into simple sentences. While learning to write, students begin to bold and copy letters/syllables, completing words and sentences, dictation, and answering questions/matching readings. The validators in the study consisted of two professors of linguistics/ elementary school, one from FKIP Unsri and the other from Malang State University. The textbook trial was conducted in three places, namely 1 TK/PAUD and 2 private educational institutions (Bimbel) for 1 month or 12 meetings (three times a week; one meeting:30 minutes). The results of the overall pilot test show students are able to identify and read letters/syllables, words, and simple sentences well. In writing, students can write letters/syllables, words, and sentences well. Keywords: textbooks, learning to read and write, elementary preschool students